POLARIZATION OBSERVABLES IN THE PROCESS (,np) ON 6Li NUCLEUS - Burkova, N.A.; Lennik, S.G. (Recent Contributions to Physics, 2021)
The asymmetry of the secondary particles in the process of two-nucleon photoemission 6Li( ,np)α has been calculated in multicluster dynamic model of 6Li nucleus with account of nucleonic and mesonic degrees of freedom.